Sensitization of Tumors for Attack by Virus-Specific CD8+ T-Cells Through Antibody-Mediated Delivery of Immunogenic T-Cell Epitopes - Sefrin, Julian P.; Hillringhaus, Lars; Mundigl, Olaf; Mann, Karin; Ziegler-Landesberger, Doris; Seul, Heike; Tabares, Gloria; Knoblauch, Dominic; Leinenbach, Andreas; Friligou, Irene; Dziadek, Sebastian; Offringa, Rienk; et al. (Frontiers in Immunology, 2019)
Anti-tumor immunity is limited by a number of factors including the lack of fully activated T-cells, insufficient antigenic stimulation and the immune-suppressive tumor microenvironment. We addressed these hurdles by developing a novel class of immunoconjugates, Antibody-Targeted Pathogen-derived Peptides (ATPPs), which were designed to efficiently deliver viral T-cell epitopes to tumors with the aim of redirecting virus-specific memory T-cells against the tumor. ATPPs were generated through covalent binding of mature MHC class I peptides to antibodies specific for cell surface-expressed tumor antigens that mediate immunoconjugate internalization. By means of a cleavable linker, the peptides are released in the endosomal compartment, from which they are loaded into MHC class I without the need for further processing. Pulsing of tumor cells with ATPPs was found to sensitize these for recognition by virus-specific CD8+ T-cells with much greater efficiency than exogenous loading with free peptides. Systemic injection of ATPPs into tumor-bearing mice enhanced the recruitment of virus-specific T-cells into the tumor and, when combined with immune checkpoint blockade, suppressed tumor growth. Our data thereby demonstrate the potential of ATPPs as a means of kick-starting the immune response against ‘cold’ tumors and increasing the efficacy of checkpoint inhibitors.